2005
DOI: 10.1158/1078-0432.ccr-05-0059
|View full text |Cite
|
Sign up to set email alerts
|

P-Cadherin Overexpression Is an Indicator of Clinical Outcome in Invasive Breast Carcinomas and Is Associated with CDH3 Promoter Hypomethylation

Abstract: Purpose: P-cadherin overexpression has been reported in breast carcinomas, where it was associated with proliferative high-grade histological tumors. This study aimed to analyze P-cadherin expression in invasive breast cancer and to correlate it with tumor markers, pathologic features, and patient survival. Another purpose was to evaluate the P-cadherin promoter methylation pattern as the molecular mechanism underlying this gene regulation. Experimental Design: Using a series of invasive breast carcinomas, P-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
197
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(212 citation statements)
references
References 38 publications
14
197
1
Order By: Relevance
“…Figure 1b shows that cell lines with higher levels of P-cadherin expression revealed an increased ability to invade through Matrigel. More importantly, these results are in agreement with what has been described in invasive primary breast tumours, showing the clinical relevance of P-cadherin expression in the diagnosis and prognosis of patients with aggressive mammary carcinomas (Peralta Soler et al, 1999;Paredes et al, 2005).…”
Section: P-cadherin Overexpression In Wild-type E-cadherin Breast Cansupporting
confidence: 90%
See 2 more Smart Citations
“…Figure 1b shows that cell lines with higher levels of P-cadherin expression revealed an increased ability to invade through Matrigel. More importantly, these results are in agreement with what has been described in invasive primary breast tumours, showing the clinical relevance of P-cadherin expression in the diagnosis and prognosis of patients with aggressive mammary carcinomas (Peralta Soler et al, 1999;Paredes et al, 2005).…”
Section: P-cadherin Overexpression In Wild-type E-cadherin Breast Cansupporting
confidence: 90%
“…Previous studies have shown that P-cadherin expression in breast carcinomas is able to identify a subgroup of lesions with a more aggressive behaviour and poor patient survival (Peralta Soler et al, 1999;Gamallo et al, 2001;Paredes et al, 2002Paredes et al, , 2004Paredes et al, , 2005Paredes et al, , 2008. Similar associations between P-cadherin expression and poor prognosis are described in other cancer models, namely endometrial, cervical, gastric and pancreatic carcinomas (Stefansson et al, 2004;Longatto Filho et al, 2005;Taniuchi et al, 2005).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Several studies have revealed that there is a good inverse correlation between methylation and gene expression. overexpression of P450 1B1 was regulated by hypomethylation in prostate cancer (25), while P-cadherin mrna expression in invasive breast carcinomas was associated with the hypomethylation of the cdH3 promoter (26). These reports suggest that the hypomethylation of specific oncogene promoters may play an important role in tumorigenesis.…”
Section: Bmentioning
confidence: 80%
“…Doubledistilled water was used instead of DNA as the blank control. Assessment of methylation status for the cases was as follows: those showing products amplified by methylated primers were considered methylated and those showing only products amplified by unmethylated primers were considered unmethylated (27,28).…”
Section: Methodsmentioning
confidence: 99%